Cone-Beam Computed Tomographic Evaluation of Prevalence and Internal Dental Morphology of Radix Entomolaris and Paramolaris in Mandibular First and Second Molars—A Retrospective Study - Mousumi Biswas; Dibyendu Mazumdar; Siddhi Agarwala; Kallol K. Saha; Kaushik Dutta (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Failure to identify root canal variations (such as extra roots) leads to poor prognosis of endodontic therapy. The prevalence of the same should be known to the clinicians. Aim: To evaluate the prevalence of radix entomolaris (RE) and radix paramolaris (RP) and its anatomic variations in mandibular first and second molars in a tertiary care center in Kolkata, using cone-beam computed tomography (CBCT). Materials and Methods: Analysis of 305 CBCT scans (126 males and 179 females; mean age 24.72 ± 8.14 years) was done to evaluate 1220 molars (610 mandibular first molars (MFM) and 610 mandibular second molars (MSM)) to detect radix. Sex, unilateral/bilateral presentation, classification, root canal length, configuration, curvature, and inter-orifice distance were recorded. The results were analyzed with Chi-square test. Result: The overall prevalence of radix entomolaris was found to be 2.8% (n = 35), in mandibular first molars—5.4% (n = 33), in mandibular second molars—0.32% (n = 2); higher in females (n = 20) (P = 0.25). Nine scans showed unilateral occurrence, and 13 showed bilateral presentation (P = 0.26). The radix showed typically shorter roots, with root divergence and curvatures, and increased intra-orifice distance. All radices had Vertucci’s Type 1 configuration. Type A radix entomolaris was found to be most prevalent—60% (n = 21), followed by Type AC—20% (n = 7). Conclusion: The results of this study recommend modifying the access cavity preparation, using magnification, and encourage the use of advanced radiographic techniques like cone-beam computed tomography whenever radix is suspected.